Restoration of MAGI-1 Expression in Human Papillomavirus-Positive Tumor Cells Induces Cell Growth Arrest and Apoptosis - Kranjec, Christian (American Society for Microbiology, 2014)
The cancer-causing high-risk human papillomavirus (HPV) E6 oncoproteins target a number of cellular proteins that contain PDZ domains. However, the role of many of these interactions in either the HPV life cycle or in HPV-induced malignancy remains to be defined. Previous studies had shown that MAGI-1 was one of the most strongly bound PDZ domain-containing substrates of E6, and one consequence of this interaction appeared to facilitate the perturbation of tight junctions (TJs) by E6. In this study, we describe the generation of a mutation, K499E, within the MAGI-1 PDZ1 domain, which is resistant to E6 targeting. This mutant allows restoration of MAGI-1 expression in HPV-positive cells and defines additional activities of MAGI-1 that are overcome as a consequence of the association with E6. The reexpression of MAGI-1 in HPV-positive cells results in an increased recruitment of ZO-1 and PAR3 to sites of cell-cell contact, repression of cell proliferation, and induction of apoptosis. While the K499E mutation does not significantly affect these intrinsic activities of MAGI-1 in HPV-negative cells, its resistance to E6 targeting in an HPV-positive setting results in more cells expressing the mutant MAGI-1 than the wild-type MAGI-1, with a corresponding increase in TJ assembly, induction of apoptosis, and reduction in cell proliferation. These studies provide compelling evidence of a direct role for the perturbation of MAGI-1 function by E6 in the HPV life cycle and in HPV-induced malignancy. IMPORTANCE It is clear that the targeting of PDZ-containing substrates by E6 is important for the normal viral life cycle and for the progression to malignancy. Nevertheless, which of these PDZ domain-containing proteins is relevant for HPV pathology is still elusive. In a previous study, we provided evidence that MAGI-1 is a sensitive proteolytic substrate for both the HPV-16 and HPV-18 E6 oncoproteins; however, the biological consequences associated with loss of MAGI-1 expression in HPV-positive cervical cancer cells are still poorly understood. Using a mutant MAGI-1, resistant to E6-mediated degradation, we show that its expression in cervical cancer cells promotes membrane recruitment of the tight junction-associated proteins ZO-1 and PAR3, represses cell proliferation, and promotes apoptosis. These findings suggest that E6-mediated inhibition of MAGI-1 function contributes to HPV pathology by perturbing tight junction assembly with concomitant stimulation of proliferation and inhibition of apoptosis.